Methods of investigating the presence of ingested lead shot in waterfowl gizzards: an improved visual technique - Pain, D J; Eon, L (Wildfowl, 1993)
Waterfowl ingest spent lead gunshot whilst feeding in shot-over wetlands. The evaluation of the degree of exposure to shot has been based on examining the gizzards of birds, killed by hunters for the presence of ingested shot. Several techniques have been employed previously for this purpose (including simple visual examination and X-ray) with varying degrees of success. In this paper we report on an improved visual examination technique and discuss the relative merits of different approaches.